Frontierism and metropolitanism in relation to development on the north shore of Lake Superior - Auger, Donald J. (My University, 1993)
The purpose of this paper is to explore some of the various influences within the metropolis-hinterland construct that were evident in the development of the area around Thunder Bay and along the north shore of Lake Superior during the period from Confederation up to about 1890. Economic, political and other metropolitan relationships in the communities along the north shore of Lake Superior were developed and controlled by various external urban centres from their early beginnings right up to the turn of the twentieth century. In this thesis I will review some of the metropolis-hinterland influences that were evident in the area. Metropolitan influences can be found throughout much of the development of the North American continent, particularly the portion that would later be called Canada. All of the early voyages of discovery, like the first fishing ventures on the Grand Banks and other places, amply demonstrate the efforts of various European capitals, or metropolises, to exert their control over the newfound hinterlands. The fur trading companies and other commercial ventures, usually acting under Royal Charters, would later exert the same metropolitan control over the broad expanses of the interior of the continent that were accessible by the extensive waterways. In both of these cases, the resident population of the hinterland would have no say in any developments that took place in the region. This aspect of metropolitanism is one that can be found at all stages of the political and economic development of the country and it figures prominently in the development of the areas along the north shore of Lake Superior and the area around Thunder Bay. It is my thesis that the resident population of the area around Thunder Bay and along the north shore of Lake Superior, whether aboriginal peoples or settlers in the area, had no say in the developments that took place in the region because all of the key decisions were made by people in far away places who controlled the various metropolitan interests that were active in the region. In the first chapter of this thesis I will review the staples and other theories, as well as the metropolis-hinterland construct as originally stated by J.M.S. Careless, Gras and others. I will also review some of the early economic and political activities that demonstrate the metropolis-hinterland relationships that arose as a result of activities in the study area. As examples of these relationships, I will look at the fur trade, the early transportation activities of the fur trade companies, and the Indian treaties of 1850. In the second chapter I will review Confederation and the purchase of Rupert’s Land. I will also discuss the development of some of the first metropolitan influences in the area, namely the economic relationships that were established as a result of mining activities, government surveys and construction of the Dawson Road. In last chapter of the thesis I will review certain economic and political initiatives during the period from Confederation up to about 1890. I will also review some of the economic activities that occurred like the development of mines, settlement, the fisheries, and the timber and grain industries. I will review the development of transportation through huge, government-sponsored projects like the Dawson Road and the Canadian Pacific Railway, and the disputes over jurisdiction in the area purchased that arose between the federal government and the governments of the provinces of Ontario and Manitoba.
Keywords: Metropolitan areas Ontario History; Frontier thesis